Implications of left atrial enlargement and patent foramen ovale creation on early surgical outcomes in patients with total anomalous pulmonary venous connection. Issue 12 (5th October 2021) - Mishra, Anand K.; Halder, Vikram; Bansal, Vidur; Patel, Ruchit; Mittal, Apeksha; Thingnam, Shyam K. S.; Singh, Rana S.; Singh, Harkant; Mahajan, Sachin; Kumar, Rupesh; Aggarwal, Pankaj; Jaswal, Vivek; et al.
Abstract: Introduction: In patients with total anomalous pulmonary venous connection (TAPVC), left atrium (LA) is small and suprasystemic pulmonary artery (PA) pressures may be present in some patients. In our study, we studied the relationship between surgical LA enlargement and patent foramen ovale (PFO) creation separately on the outcomes of patients with TAPVC. Materials and methods: Out of the 130 patients operated in our institute between January 2014 and December 2020, LA was enlarged in 60 patients. LA enlargement was done using a larger patch for atrial septal defect (ASD) closure. Thus, the LA volume was increased by shifting the patch towards the right atrium (RA). Suprasystemic or high PA pressures were present in 60 patients. In 33 patients, PFO was created. Early surgical outcomes were determined on the basis of vasoactive inotropic score (VIS), hours of ventilation, hours of inotropic support, intensive care unit (ICU) stay, and hospital stay. Result: Between the LA enlarged and nonenlarged group there was statistically significant less VIS score (18 [13–27.5] vs. 24 [18–30], p value .019), hours of ventilation (23 [16–46.5] vs. 26 [18–60], p value .039), hours of inotropic support (45.5 [30–72] vs. 55 [38–84], p value .038), and ICU stay (7 [5–9] vs. 8 [7–10] p value .0352) and statistically nonsignificant less hospital stay (11.5 [9–13] vs. 12 [9–14], p value .424). In patients with preoperative suprasystemic or high PA pressures, there was a statistically significant less VIS score (16 [11–23.5] vs. 18 [13–25], p value .044), hours of ventilation (20 [14–37] vs. 22 [18–39], p value .038), hours of inotropic support (34 [29.5–71] vs. 38 [30–78], p value .042), and hospital stay (9 [5–12] vs. 11 [9–14], p value .038) and statistically nonsignificant less ICU stay (7 [5.5–9] vs. 7 [6–9], p value .886) in the group with a PFO with respect to the other group in which no PFO was created. Conclusion: In patients with TAPVC, LA can be enlarged by using a large ASD patch and thus shifting the septum towards RA. Early surgical outcomes were improved with LA enlargement. In patients with suprasystemic or high PA pressures, leaving a PFO improved the postoperative outcomes.